Transformasi Regulasi Pengembangan dan Penguatan Sektor Keuangan Otoritas Jasa Keuangan: Sebuah Evaluasi dan Rekomendasi - I Made Dwi Hita Darmawan; Ida Bagus Ardhi Putra (Jurnal Eksplorasi Akuntansi, 2024)
This research aims to exploratively evaluate the implementation of the Financial Sector Development and Strengthening Law (P2SK Law) of the Financial Services Authority (OJK), which has been little researched. The research method used a qualitative approach with interviews to explore in depth. Informants consisted of OJK representatives, banking representatives, and customers. Data were analyzed thematically for key findings and their correlation with theory. The results show OJK has socialized the law, but there are challenges adapting to the complex rules, requiring additional investment in technology and human resources. Recommendations include increased socialization, cooperation with financial institutions, digital education, close supervision, technological innovation, and consultation forums.